Automated visual assembly inspection - Bouman, Charles A., author; Maciejewski, Anthony A., author; Tretter, Daniel, author; Khawaja, Khalid W., author (Colorado State University. Libraries, 2002)
This chapter has discussed an intelligent assembly inspection system that uses a multiscale algorithm to detect errors in assemblies after the algorithm is trained on synthetic CAD images of correctly assembled products. It was shown how the CAD information of an assembly along with fast rendering techniques on specialized graphics machines can be used for the automation of the work-cell camera and light placement. The current emphasis in the manufacturing industry on concurrent engineering will only cause this integration between the CAD model of products and its manufacturing inspection to grow in value.